Towards a 'global educational justice' research paradigm: cognitive justice, decolonizing methodologies and critical pedagogy - Jennifer Chan-Tiberghien (Globalisation, Societies and Education Vol. 2, No. 2, July 2004, 2004)
This article challenges three predominant narratives on educational globalization educational restructuring,' `educational institutionalism,' and `educational multilateralism'-and shows how they have largely failed to propose alternatives to the neoliberal order. I connect two disparate literatures on educational globalization and anti-globalization social movements-to argue that the alternative globalization movement performs global citizenship education through critical pedagogy, cognitive justice, and decolonizing methodologies. To arrive at a multi-layered model of citizenship, what is needed is not only critical pedagogy, but a fundamental critique of the cognitive injustice inherent within the hegemonic neoliberal ideology by re-asserting the diversity of value systems and restoring subjugated knowledges through alternative methodologies. Drawing upon my participant observation at the 2003 anti-G8 Summit in France and anti-World Trade Organization meeting in Mexico, as well as the fourth World Social Forum in India, I propose a new research program on global educational justice.